Meningkatkan Kepercayaan Diri dan Hasil Belajar dengan Menggunakan Metode Every One is Teacher Here pada Mata Kuliah Sejarah Pendidikan Indonesia - Melinda, Cicilia (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2017)
The problem in this study is weather to use the method of every one is teacher here can improved the self- confidentand learning outcome in the educational Indonesia history. The purpose of this reseach is to description weather the every one is teacher here methods can improve self- convidence and student learning outcomes in the educational Indonesian history. The method is descriptive method, the form of reseach is classroom action reseach, the nature of collaborative reseach, data analysis technique using the average calculation. The result showed that the educational hindonesian history using every one is teacher here method can improve students learning outcome. Can be seen 1) The self confident by using the method of every one is teacher here first cycle average 2,22, the self confident by using the method of every one is teacher here second cycle average 3,22. 2) The learning outcome of student in the educational Indonesian history by using the method of every one is teacher here first cycle average 61,90. Second cycle student learning outcomes on average 81,33, learning out comes of student increased by 31,43.